Pendampingan Digital Marketing, Media Sosial Dan Modal Usaha Terhadap Forum UMKM Tajur Halang Kabupaten Bogor - Muharam, Hari; Gursida, Hari; Hidayat Susilowati, Isnurrini; Widiyanti, Wiwik; Tuti Alawiah, Enok; Widasiwi, Herlin (Jurnal Abdimas Ekonomi dan Bisnis, 2023)
The Tajur Halang SME Forum is an organization that consists of business operators who reside in the Tajur Halang District of Bogor Regency.These operators face challenges in marketing their products, introducing them to customers, and securing business capital for ongoing operations.The aim of this community service is to offer training in digital marketing, social media utilization for product marketing, and accessible methods for acquiring business capital.The approach involves a series of training sessions that start with group forum discussions, a situational analysis of the partners, pre-tests, main training activities, and post-tests.The results of these activities show an improvement in the partners' knowledge, skills, and abilities in digital marketing, using Instagram for branding and brand awareness, managing engagement, and accessing business capital